Product range optimization – case study - Barsan, Simona; Sima, Mihaela (Studies and Scientific Researches. Economics Edition, 2010)
The paper presents the optimizing procedure of the product range manufactured by a company which operates in the area of production and sales of the milling and bakery products. The paper authors have taken this company as an example since the products it manufactures and commercializes address to population and are required to meet both qualitative and quantitative market requirements. After a brief overview of the company, one analyses its production capacity, staff structure and distribution as well as the concern of the company for the employees’ training in its activity field, so as to fulfill all the necessary and required conditions for developing a qualitative activity. The analysis continues with: the cost of the product before optimization, software presentation and computerized optimization procedure, the selection of the products to be optimized, data collection, the optimization procedure, results obtaining and analysis, choosing the optimal solution for the analyzed products analysis and for the future competitiveness of the company.